Research on Calculation Method of Rain Load on Structures Based on Discrete Particle Model. (2nd November 2022) - Ling, Hongjie; Wang, Zhidong; An, Shuai; Sun, Guohuai; Yan, Yangyue
Abstract : With the frequent occurrence of extreme weather, the rain load of structures under high wind speeds accompanied by heavy rainfall conditions has become a hot issue for research. In this paper, based on the discrete particle model, the raindrop impact load correction formula is proposed. A rapid calculation method for the rain load of structures is formed through experimental verification. And the forecasting program is developed independently to complete the calculation of rain load per unit flat plate under different wind speed and rainfall intensity combination states. The rain load correction coefficient Δ C w is defined as the dimensionless coefficient of the rain load per unit area of the flat plate in a fully developed rain field driven by wind speed. The rain load is factored into the wind load calculation formula by way of the correction coefficient Δ C w to form the calculation formula for the rain load of structures. The results show that Δ C w has little correlation with wind speed but is closely related to rainfall intensity R . The calculation formula for Δ C w about rainfall intensity is fitted. When rainfall intensity R = 709.2 mm/h, Δ C w is approximately 22.3%. The research results in this paper provide theoretical and technical support for guiding the rapid calculation of rain load on structures.